Remote Sensing: Capabilities And Legal Issues - Othman, Mohd Bahrin bin (Journal of Malaysian and Comparative Law, 2000)
In this brief paper, we will first look into the capabilities of the "remote sensing satellites" both in terms of technological and economical considerations. The second part of this paper shall discuss the position of the "remote sensing satellites" from the eyes of the international law especially the legal principles of the United Nations.